Eksplorasi Pengetahuan Guru Inklusi Mengenai Pendidikan Seksual di Masa Pubertas Remaja Putri dengan Disabilitas Intelektual Ringan - Agfa Aghnia Nadirah; Langgersari Elsari Novianti; Hendriati Agustiani (Jurnal Psikologi Udayana, 2021)
Sexual education at puberty is needed for young women with mild intellectual disabilities (ID) to help with puberty. Through sexual education, young women can have a better understanding of the changes that occur in their bodies and the right behavior to show in the social environment. This study aims to determine the knowledge of inclusive teachers about sexual education at puberty for young women with mild intellectual disabilities. This research was conducted using the principles of qualitative research. Data obtained based on interviews using telephone media to 4 inclusive school teachers in Bandung. Data were analyzed using thematic analysis techniques. The results show that knowledge about the characteristics of ID is still not mastered by all teachers. Knowledge about how to teach students with mild ID in the academic settings and the characteristics of puberty is owned by the four teachers based on their experience. However, all teachers do not yet have complete knowledge about the scope of sexual education material that needs to be provided as well as how to provide effective sexual education for young women with mild ID. Further research can be carried out to develop an intervention program design to improve the knowledge and skils of inclusive teachers to provide sexual education at puberty